2022
DOI: 10.4271/2022-01-0675
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Distribution of Battery Electric and Fuel Cell Electric Buses in a Metropolitan Public Transport Network

Abstract: The need to decrease greenhouse gases emissions in the transport sector has resulted in the requirement for zero emission technologies in city centre bus fleets. Currently, battery electric buses are the most common choice, with both single deck and double deck vehicles in regular use. However, long-term operational capabilities are still largely unknown and unreported. Hydrogen fuel cell electric buses are an emerging zero emission technology that have the potential to complement a battery electric bus fleet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The Matlab simulations focused on the speed profiles of the vehicles. Blades et al [58] conducted a simulation study and found that hydrogen fuel cell buses showed higher range and operating time compared to battery electric buses. In Finland, a computational tool was developed and tested using standard test cycles on two 100 km routes in the center of Manhattan.…”
Section: Simulation Approaches For Beb Energy Predictionmentioning
confidence: 99%
“…The Matlab simulations focused on the speed profiles of the vehicles. Blades et al [58] conducted a simulation study and found that hydrogen fuel cell buses showed higher range and operating time compared to battery electric buses. In Finland, a computational tool was developed and tested using standard test cycles on two 100 km routes in the center of Manhattan.…”
Section: Simulation Approaches For Beb Energy Predictionmentioning
confidence: 99%